A-180 A Preliminary Study of Prospective Memory Performance and Medication Adherence Among Young Adults. (28th August 2020) - T, Glover; E, Flores; L, Williams; S, Shorter; L, Childers; K, Mollenkopf; L, Barela; J, Sawyer; M, Barnett
Abstract: Objective: Medication adherence is a significant problem concerning the proliferation of many illnesses, and prospective memory—that is, memory to carry out an intended future action—may play a role in whether individuals take their medications (Osterberg & Blaschke, 2005; Zogg, Woods, Sauceda, Wiebe, & Simoni, 2012). Current research on prospective memory and medication adherence suggests that individuals take medication more efficiently when associated with a specific event, rather than when associated with the passage of time (Zogg et al., 2012). The purpose of this preliminary study was to investigate the relationship between prospective memory and medication adherence. Method: Young adults (N = 16, 18–30 years) who identified as regularly taking prescription medications completed the Morisky Medication Adherence Scale (MMAS) and the Virtual Kitchen Protocol, which includes prospective memory tasks with both event-based and time-based cues. Results: Higher scores on event-based cues were associated with better medication adherence among young adults (p = .005). However, performance on time-based cues was not associated with medication adherence. Conclusions: Event-based prospective memory cues are associated with higher medication adherence among young adults. Furthermore, event-based prospective memory cues may be more indicative of medication adherence in young adults, when compared to time-based prospective memory cues. Individuals are generally better at event-based cues, particularly because they involve automatic retrieval processes (Zogg et al., 2012). On the other hand, time-based cues require more monitoring and greater time estimation (Zogg et al., 2012). Overall, it is evident that prospective memory is an important contributor to medication adherence among young adults.